Alienated Subjectivity in Sylvia Plath’s The Bell Jar (Journal of Population and Development, 2024)
This article has analyzed Sylvia Plath’s The Bell Jar to explore the resilient personality of Esther Greenwood that exemplifies the image of nonconformist women in the patriarchal society of America. Esther has been prepared to fight against the standards of femininity induced in the personality of general women. She stands out of the crowd for her dignity. The objective of the paper has been to investigate into the characters created to reveal diverse images of women in the American society. The key finding of the research is that Esther during her professional journey undergoes diverse complications primarily created for women to suffer from and imposed upon them by the male-dominated society. She has not experienced any solace of life neither at home has nor she been satisfied in the society at large. Therefore, she feels isolated. Her alienation leads to attempting for suicide as she takes it as the way of relief and mental satisfaction. Her decision of taking her own life implies her desperation and disinterestedness in the world controlled by men. By using the concept of Betty Friedman as expressed in The Feminine Mystique, this paper has been inscribed to reflect on the confused personality of Esther.